Evaluasi Program Pembinaan Unit Kegiatan Mahasiswa (UKM) Tenis Lapangan Universitas Negeri Surabaya - Tri Nida Nur Jayanti; Panji Bana; Pudjijuniarto Pudjijuniarto; Heri Wahyudi (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
This study aims to evaluate the coaching program of the Tennis Student Activity Unit (UKM) at the State University of Surabaya using the CIPP (Context, Input, Process, Product) evaluation model. The research background is based on the absence of a structured evaluation of the coaching program, despite the UKM Tennis team’s achievements at regional and national levels. This research applies a mixed-method approach with descriptive quantitative and qualitative methods. The research subjects consist of 33 participants, including UKM administrators, coaches, and athletes. Data were collected through questionnaires, interviews, observations, and documentation. The findings reveal that: (1) The Context component falls into the “very good” category, indicating the alignment of vision, mission, and coaching objectives, although long-term  program planning requires improvement; (2) The Input component is also considered good, supported by qualified coaches and university support; (3) The Proces component is good, with regular training sessions and adequate monitoring; (4) The Product component shows positive results, reflected in the athletes’ achievements in various competitions.